A case study of 10 patients administered HBOC‐201 in high doses over a prolonged period: outcomes during severe anemia when transfusion is not an option. Issue 5 (1st May 2020) - Zumberg, Marc; Gorlin, Jed; Griffiths, Elizabeth A.; Schwartz, Garry; Fletcher, Bradley S.; Walsh, Katherine; Dao, Kim‐Hien; Vansandt, Amanda; Lynn, Mauricio; Shander, Aryeh
ABSTRACT: BACKGROUND: Hemoglobin‐Based Oxygen Carriers (HBOCs) can act as an "oxygen bridge" in acute severe anemia when transfusion is indicated, but not possible. We present data on 10 Expanded Access (EA) patients treated with high cumulative doses of Hemopure (HBOC‐201), to assess the ability of HBOC‐201 to safely treat life threatening anemia in situations where high volumes of product were administered over an extended period of time. STUDY DESIGN AND METHODS: Inclusion in this study required that the patient receive at least 10 units of HBOC‐201 between 2014 and 2017 under the FDA‐sanctioned EA program. Depending on a patient's geographical location, treatment with HBOC‐201 was obtained through either a single patient emergency Investigational New Drug (IND) application, or an intermediate size population IND. Of the 41 patients who were treated during this period, 10 patients received 10 or more units of the product. Data were obtained from medical records. RESULTS: Treatments with HBOC‐201 started within 24 hours of signing consent and were administered at an average rate of 1.99 (SD 0.17) units per day over a mean of 8.2 days (SD 2.9), during which patients received on average 16.2 units (SD 5.7 units) of HBOC‐201. The median pre‐treatment nadir corpuscular hemoglobin (Hb) concentration was 3.3 (SD 0.9) g/dL and post‐treatment Hemoglobin was 7.3 (SD 1.7) g/dL. Common side effects included methemoglobinemia, gastrointestinal symptoms, and hypertension. However, no product‐related serious adverse events (SAEs) were noted. All patients survived. CONCLUSIONS: Administration of HBOC‐201 over an extended period is a feasible and safe oxygen bridge for severely anemic patients who cannot be transfused with RBC.